Critical Pedagogy: Future and Hope - Luital, Chandra; Dahal, Niroj; Pant, Binod Prasad (Journal of Transformative Praxis, 2022)
Critical pedagogy is a pedagogical philosophy and social movement founded on the notion of critical social theories and paradigms. Critical pedagogy encompasses a wide range of topics, including future and hope. Whilst developing educational programs, implementing pedagogies, and responding to humanitarian crises, critical pedagogy becomes a basis for examining deep-seated values, beliefs and assumptions that might otherwise challenge empowering, equitable and socially just educational and social systems (Luitel & Dahal, 2020). Such a process is, without doubt, an important component of renewing education and culture. Politics is at the heart of critical pedagogy (McLaren & Leonard, 1993). Hence, in this editorial, we attempt to highlight critical pedagogy: future and hope of the Freirean concepts of critical pedagogy (1921-1997). Education as “banking”, liberatory pedagogy, education is political, critical pedagogy is not Eidos, pedagogy of hope, critical reflection as/for conscientization, critical pedagogy in the classroom and research with people instead of research on people are some of the key ideas that are discussed in this editorial. Our editorial concludes with a brief summary of the original articles that are covered in this issue.